Maturation of the Oral Microbiome in Caries-Free Toddlers: A Longitudinal Study. (February 2020) - Kahharova, D.; Brandt, B.W.; Buijs, M.J.; Peters, M.; Jackson, R.; Eckert, G.; Katz, B.; Keels, M.A.; Levy, S.M.; Fontana, M.; Zaura, E.
Understanding the development of the oral microbiota in healthy children is of great importance to oral and general health. However, limited data exist on a healthy maturation of the oral microbial ecosystem in children. Moreover, the data are biased by mislabeling "caries-free" populations. Therefore, we aimed to characterize the healthy salivary and dental plaque microbiome in young children. Caries-free (ICDAS [International Caries Detection and Assessment System] score 0) children ( n = 119) and their primary caregivers were followed from 1 until 4 y of child age. Salivary and dental plaque samples were collected from the children at 3 time points (T1, 1 y old; T2, 2.5 y old; and T3, 4 y old). Only saliva samples were collected from the caregivers. Bacterial V4 16S ribosomal DNA amplicons were sequenced using Illumina MiSeq. The reads were denoised and mapped to the zero-radius operational taxonomic units (zOTUs). Taxonomy was assigned using HOMD. The microbial profiles of children showed significant differences ( P = 0.0001) over time. Various taxa increased, including Fusobacterium, Actinomyces, and Corynebacterium, while others showed significant decreases (e.g., Alloprevotella and Capnocytophaga ) in their relative abundances over time. Microbial diversity and child-caregiver similarity increased most between 1 and 2.5 y of age while still not reaching the complexity of the caregivers at 4 y of age. The microbiome at 1 y of age differed the most from those at later time points. A single zOTU ( Streptococcus ) was present in all samples ( n = 925) of the study. A large variation in the proportion of shared zOTUs was observed within an individual child over time (2% to 42% of zOTUs in saliva; 2.5% to 38% in dental plaque). These findings indicate that the oral ecosystem of caries-free toddlers is highly heterogeneous and dynamic with substantial changes in microbial composition over time and only few taxa persisting across the 3 y of the study. The salivary microbiome of 4-y-old children is still distinct from that of their caregivers.